Environmental Literacy Assessment Among Economic Education Students at Kuningan University - Nur Umamah; Silpa Nabilah Sajidin; Amelia Pebrianti; Tesha Rismayanti; Deden Agustira (THE PRESTISE, 2026)
Environmental literacy has become a critical competency in higher education, particularly in shaping future educators who will influence environmental awareness across society. This study investigates the environmental literacy levels among Economic Education students at Kuningan University, Indonesia, recognizing their pivotal role as future change agents in educational settings. Using a descriptive quantitative approach, data were collected from students through a structured questionnaire assessing five key dimensions: environmental knowledge, attention to environmental issues, environmental sensitivity, attitudes toward the environment, and pro-environmental behavior. The instrument was adapted from the Middle School Environmental Literacy Survey to ensure validity and reliability in measuring these interconnected components of environmental literacy. Results revealed a concerning gap between theoretical understanding and practical environmental action. While students demonstrated adequate environmental knowledge, they exhibited significantly lower levels in practical dimensions including attention, sensitivity, attitudes, and behavior. This discrepancy suggests that cognitive understanding alone does not automatically translate into environmental consciousness or sustainable practices. The study concludes that environmental literacy education needs fundamental strengthening through experiential learning approaches, community-based environmental projects, and comprehensive campus-wide sustainability initiatives. These interventions are essential to bridge the knowledge-action gap among future educators, enabling them to model and promote genuine environmental stewardship in their professional careers. The findings carry significant implications for curriculum development and pedagogical approaches in higher education institutions committed to advancing environmental sustainability.